Red flags to diagnose infiltrative cardiomyopathies - E. V. Reznik; T. L. Nguyen; D. V. Ustyuzhanin; A. N. Semyachkina; M. A. Shkolnikova (Российский кардиологический журнал)
Infiltrative cardiomyopathies are a group of diseases characterized by the deposition of abnormal substances in heart tissues, which leads to thickening of the walls or dilation of chambers with a secondary decrease in wall thickness and the development of diastolic, less often systolic, ventricular dysfunction. Most often, these are progressive diseases that, in the absence of adequate therapy, have an unfavorable prognosis. Clinical manifestations of infiltrative cardiac diseases are variable, which often leads to diagnostic difficulties and errors. In most cases, specific laboratory and morphological tests are required to confirm or clarify the diagnosis. Early diagnosis is critical to initiating therapy and improving patient prognosis. This article provides characteristic signs and symptoms, the so-called "red flags", making it possible to suspect infiltrative cardiomyopathies, diagnose them at an early stage and start life-saving therapy.